UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SD NEGERI 2 RAJABASA JAYA KOTA BANDAR LAMPUNG - Effendi, Hasan (UNISAN JURNAL, 2024)
The purpose of this study was to find out the efforts of the madrasa head in improving the quality of learning at SDN 2 Rajabasa Raya. This study uses a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used is observation, interview and documentation techniques. Head of Sekolah Providing guidance/motivation to students is very important for students, because students come to SDN 2 Rajabasa Raya not to play games, but to study. Learning will be more meaningful, when the student has a passion for learning. The Head of SDN 2 Rajabasa Raya, always strives to improve the quality of teaching and learning, with efforts such as: Always seeking teachers according to their respective competencies, Always holding or attending training on the ability to manage KBM, Always providing guidance/motivation to students, Always seeking learning infrastructure facilities adequate, always supervise the course of the KBM.